Analisis Nilai Moral dalam Novel Kami Bukan Jongos Berdasi Karya J. S Khairen sebagai Alternatif Bahan Ajar Sastra di SMK PGRI 3 Nganjuk (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This research is motivated by problems regarding the decline in moral values ​​that still often occur in everyday life. To be able to minimize problems regarding poor morale, especially students, namely through learning activities at school. Literary works can be used by educators to instill, shape, and develop the morale of students. One of the literary works that can be used is the novel We're Not Jongos Berdasi. This study aims to 1) describe the manifestation of the moral values ​​contained in the novel We're Not Jongos Berdasi by J.S Khairen, 2) describe the suitability of the novel We're Not Jongos Berdasi by J.S Khairen as an alternative material for teaching literature at SMK PGRI 3 Nganjuk. This study uses descriptive qualitative methods, data collection techniques are documentation and interviews. The results of this study are 1) The moral values ​​contained in the novel We're Not Jongos Berdasi are divided into three, namely the relationship between humans and God, the relationship between humans and themselves, and the relationship between humans and other humans. The moral value of man's relationship with God consists in thanking God and remembering God. The human relationship with oneself consists of self-confidence, unyielding, patient, firm, independent, and regretful. Human relations with other humans consist of caring for others, polite, honest, maintaining feelings, openness, and greeting. 2) Our novel is not Jongos Berdasi, suitable for use as an alternative literature teaching material at class XI SMK PGRI 3 Nganjuk. This is because the novel has fulfilled the aspects of language, psychology, and cultural background.